Biased dual-exfoliation technique with expanded graphite for high-quality few-layer graphene sheets in electrochemical exfoliation - Lim, Sungmook; Lingappan, Niranjanmurthi; Lee, Wonoh (Carbon Letters, 2025)
Efforts to mass-produce high-quality graphene sheets are crucial for advancing its practical and industrial applications across various fields. In this study, we present an innovative electrochemical exfoliation method designed to enhance graphene quality and increase yield. Our approach combines two key techniques: expanding the tightly packed graphite interlayer used as the electrode medium and precisely controlling voltage polarity. The dual-exfoliation technique optimizes the use of anions and cations of varying sizes in the electrolyte to facilitate meticulous intercalation, allowing ions to penetrate deeply and evenly into the graphite interlayer. The newly designed dual-exfoliation technique using biased switching polarity minimizes the generation of oxygen-containing radicals, while the incorporation of expanded graphite accelerates exfoliation speed and reduces oxidation, maintaining high graphene purity. With these improvements, we produced 1–3 layer graphene sheets with minimal defects (I D / I G ≈ 0.13) and high purity (C/O ratio ≈ 20.51), achieving a yield 3.1 times larger than previously reported methods. The graphene sheets also demonstrated excellent electrochemical properties in a three-electrode system, with an electrical conductivity of 92.6 S cm −1 , a specific capacitance of 207.4 F g −1 , and a retention of 94.8% after 5,000 charge/discharge cycles, highlighting their superior stability and performance. Graphical abstract